A synergistic photothermal and photocatalytic membrane for efficient solar-driven contaminated water treatment. Issue 21 (12th October 2021) - Ding, Yang; Feng, Kai; He, Panpan; Liu, Ning; Hao, Liang; Gong, Jiang; Niu, Ran; Qu, Jinping
Abstract : A synergistic photothermal and photocatalytic membrane is constructed by facilely dip-coating an MXene and graphitic carbon nitride on cotton cloth for solar evaporation and degradation of organic pollutants in source water at the same time. Abstract : Solar evaporation is considered as a promising approach for harvesting freshwater from non-potable water utilizing sustainable solar energy. Integrating the photocatalytic effect into solar vapor generation is beneficial for the substantial augmentation of solar energy utilization for freshwater production and dealing with polluted water when it is used as source water. In this work, a synergistic photothermal–photochemical hybrid membrane is prepared by facilely dip-coating three-dimensional porous carbon nitride (CN) and a two-dimensional MXene on non-woven cotton cloth. The obtained hybrid membrane possesses high light absorption in the whole solar spectrum, a decreased band gap, excellent photothermal conversion accompanied by a reduced non-radiative reflection loss, and enlarged photocurrent by forming a Schottky junction between the MXene and CN under simulated solar light. With the combined merits above, the hybrid membrane shows excellent photocatalytic performance and solar steam generation. Typically, the hybrid membrane degrades 95% Rhodamine B, 92% crystal violet and 72% methyl orange at 3 mg L −1 under 1 kW m −2 irradiation within 60 min. The water evaporation rate is up to 2.30 kg m −2 h −1 with a solar-to-vapor conversion efficiency of 98.9% under one-sun irradiation. Significantly, a large-scale solar conversion device is constructed for outdoor experiments to simultaneously harvest freshwater from contaminated water and degrade organic dyes in source water. The daily freshwater production rate is 5.7 kg m −2, meeting the requirement of two adults. This work demonstrates the promising potential of the hybrid membrane for potable water production and contaminated water treatment within one device and opens an avenue for application in energy conversion and storage.